ChemInform Abstract: Spontaneous Oxygenation of Siloxy‐N‐silylketenimines to α‐Ketoamides. Issue 32 (22nd July 2016) - Sasaki, Michiko; Ando, Masafumi; Kawahata, Masatoshi; Yamaguchi, Kentaro; Takeda, Kei
Abstract: α, β‐Unsaturated siloxy‐N‐silylketenimines, in situ generated from O‐silyl cyanohydrins, are conveniently and efficiently transformed to the corresponding α‐ketoamides by short exposure to air or oxygen under extremely mild reaction conditions.